Factors influencing purchasing of green Islamic bank products: Arabic term as the moderator - Pitchay, Anwar Allah; Mohd Saad, Lina Farhanah; Ganesan, Yuvaraj; Shaharudin, Muhammad Shabir; Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hassanudin (Routledge, Taylor & Francis Group, 2025)
This study aims to investigate factors that influence Islamic bank clients’ intention to purchase Islamic bank green products. The investigated factors are based on Theory of Planned Behaviors (TPB), which is the attitude of Islamic bank clients, subjective norms of Islamic bank clients, and perceived behavioral control of Islamic bank clients toward the intention of Islamic bank clients to purchase Islamic bank green products. The study also investigates the moderating effect of Arabic term in the relationship between TPB factors (attitude of Islamic bank clients, subjective norms of Islamic bank clients, and perceived behavioral control of Islamic bank clients) and the intention of Islamic bank clients to purchase Islamic bank green products. A quantitative method was used to analyze data and 258 Islamic bank clients participated in a self-administered questionnaire. The questionnaire is distributed based on a convenience sampling technique, through email and social media platforms. The data is analyzed by using SPSS and SmartPLS software. The results show three (3) concepts, which are the attitude of Islamic bank clients, subjective norms of Islamic bank clients and perceived behavioral control of Islamic bank clients, have a positive relationship and significant effect toward the intention of Islamic bank clients to purchase Islamic bank green products. Whereas Arabic term was not found significant to moderate the relationship attitude of Islamic bank clients, subjective norms of Islamic bank clients and perceived behavioral control of Islamic bank clients and the intention of Islamic bank clients to purchase Islamic bank products.